994 The Evolving Role of Interventional Radiology in the Management of Diverticular Abscesses: A Review of Practice at University Hospital Waterford Over 10 Years. (19th August 2022) - Murphy, B; McLoughlin, M
Abstract: Background: Historically, intra-abdominal sepsis was managed conservatively, or with operative intervention, which is associated with significant morbidity and mortality. Image-guided drainage of abscesses or collections provides a useful alternative and has become more common with the increasing prominence of Interventional Radiology, offering faster recovery, reduced length of hospital stay and cost of treatment. Modern procedural tools, techniques and expertise allow high levels of percutaneous drainage success. The scope of practice has widened to include targets which previously wouldn't have been amenable to drainage. Aim: To quantify the use and benefit of IR drainage for complicated diverticulitis at University Hospital Waterford over the past ten years. The size and location of collections drained throughout the ten years was observed. Length of hospital stay for each mode of management (conservative, percutaneous drainage and surgical) was used as an endpoint to assess morbidity. Method: Using NIMIS, all CT abdomen/pelvis reports containing the words "abscess" or "collection", and "diverticul" over the past 10 years was compiled. These patients were categorised by their management, into groups of conservatives, percutaneous drainage, surgical intervention, or a combination of these. NIMIS was used to determine who underwent IR drainage. T-pro, theatre logbooks and patient notes were used to determine who had surgical management, and iPMS was used to assess length of hospital stay. Results: IR drainage has become more common year-on-year in UHW and was shown to be more effective for all abscess sizes as compared with conservative management, as outlined in the table shown